SYSTEMATIC LITERATURE REVIEW ON NEUROSCIENCE OF CONCEPTUAL LEARNING IN MATHEMATICS - Wan Norliza Wan Bakar; Noor Suzana Shahidan (Jurnal Penyelidikan Sains Sosial, 2021)
Conceptual learning in Mathematics is defined as the tactical reasons why operation regarding numerical value works as they do. Neuroscience in Mathematics explained about brain activation that occurs while studying the subject. A systematic literature studies have been done to analyze past studies related to pin point the Neuroscience of Conceptual Learning in Mathematics. Literature studies from Google Scholar, ERIC, ScienceDirect and Springer have been used to get informations on these relationship. The overall findings shown that it is reassuring to observe that the current emphasis of the significance of inhibitory management technology and arithmetic, which emerges from the cognitive neuroscience studies, is totally consistent with older practice to inspire students to take a ‘ready time’ earlier than responding throughout technology lessons. While there is already vast experience amongst instructors that inhibitory management is a foundational ability in arithmetic and cognitive neuroscience has proof to improve this conviction and similarly enhance practice.